When spittle speaks: the semiotics of saliva and the moral body in Ígálâ communication - Ẹ̀jẹ̀bá Salem Ǒchála; Sado, Austen Amechi (Linguistik Online, 2025)
This paper explores the ethnopragmatic significance of saliva (ítọ́) in the communicative and ritual life of the Ígálâ people of central Nigeria. More than a biological fluid, saliva functions as a semiotic medium that materializes spiritual force, enacts blessing and cursing, encodes moral judgment, and affirms hierarchy. Acts of spitting, whether gentle or forceful, operate as embodied speech acts that link body, language, cosmos, and moral order. Drawing on Natural Semantic Metalanguage (NSM) and Conceptual Metaphor Theory (CMT), the study renders Ígálâ meanings cross-culturally accessible and highlights metaphorical schemas. These frameworks reveal how saliva grounds communicative practice in embodied experience while extending into domains of conflict, bonding, purification, emotion, and wisdom. Although centered on Ígálâ, the analysis points toward a broader comparative agenda: future research might examine how Yoruba, Igbo, Hausa, Akan, Zulu, and other African traditions deploy saliva or related substances in blessing, covenant, healing, or censure. By integrating ethnopragmatics with semiotic theory, the study shows that meaning in Ígálâ is inseparable from embodied practice, where mouth, body, and spirit converge to generate the moral substance of speech.